Community Health Workers' Experiences in Strengthening the Uptake of Childhood Immunization and Malaria Prevention Services in Urban Sierra Leone - Ishizumi, Atsuyoshi; Sutton, Roberta; Mansaray, Anthony; Parmley, Lauren; Eleeza, Oliver; Kulkarni, Shibani; Sesay, Tom; Conklin, Laura; Wallace, Aaron S.; Akinjeji, Adewale; Toure, Mame; Lahuerta, Maria; et al. (Frontiers in Public Health, 2021)
Introduction Community health workers (CHWs) play an integral role in Sierra Leone’s health systems strengthening efforts. Our goal was to understand CHWs’ experiences of providing immunization and malaria prevention services in urban settings and explore opportunities to optimize their contributions to these services. Methods In 2018, we conducted an exploratory qualitative assessment in the Western Area Urban district, which covers most of the capital city of Freetown. We purposively selected diverse health facilities (i.e., type, ownership, setting) and recruited CHWs through their supervisors. We conducted eight focus group discussions (FGD) with CHWs, which were audio-recorded. The topics explored included participants’ background, responsibilities and priorities of urban CHWs, sources of motivation at work, barriers to CHWs’ immunization and malaria prevention activities, and strategies used to address these barriers. The local research team transcribed and translated FGDs into English; then we used qualitative content analysis to identify themes. Results Four themes emerged from the qualitative content analysis: (1) pride, compassion, recognition, and personal benefits are important motivating factors to keep working as CHWs; (2) diverse health responsibilities and competing priorities result in overburdening of CHWs; (3) health system- and community-level barriers negatively affect CHWs’ activities and motivation; (4) CHWs use context-specific strategies to address challenges in their work but require further support. Conclusion Focused support for CHWs is needed to optimize their contributions to immunization and malaria prevention activities. Such interventions should be coupled with systems-level efforts to address the structural barriers that negatively affect CHWs’ overall work and motivation, such as the shortage of work supplies and the lack of promised financial support.